Histological and Microstructural Evaluation of Strontium Apatite-Reinforced Mineral Trioxide Aggregate Composites in Experimental Rat Tibial Bone Defects - Oztekin, Faruk; Macit, Cevher Kursat; Gurgenc, Turan; Toprak, Zeynep; Dundar, Serkan; Ayik, Merve; Ozercan, Ibrahim Hanifi (Mdpi, 2026)
Mineral trioxide aggregate (MTA) is a calcium silicate-based endodontic biomaterial widely used for its biocompatibility, sealing ability, and osteoconductive potential; however, further enhancement of its bone regenerative capacity without compromising structural stability remains of interest. Strontium apatite (SrAp), a bioactive calcium phosphate phase structurally analogous to bone mineral, may promote osteogenic activity and bone regeneration. In this study, standardized cylindrical defects (2.5 mm diameter, 4 mm depth) were created in the right tibial metaphysis of systemically healthy rats and allocated to four groups: empty defect (control), pure MTA, 25SrAp-MTA, and 50SrAp-MTA. SrAp nanoparticles were synthesized hydrothermally and incorporated into the MTA matrix at predefined weight fractions. Materials were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). After 8 weeks, tibial specimens were harvested and processed for H&E histology; fibrous tissue formation, new bone formation, and osteoblastic cell presence were semi-quantitatively scored. XRD and FT-IR confirmed that SrAp incorporation preserved the fundamental Ca-silicate phase architecture and hydration chemistry of MTA, indicating chemical and crystallographic stability. SEM-EDX demonstrated progressive microstructural densification with increasing SrAp content, with reduced intergranular porosity and homogeneous SrAp distribution. Histologically, both SrAp-MTA groups exhibited significantly higher new bone formation and osteoblastic activity than untreated controls (p < 0.05), while fibrotic tissue formation did not differ significantly among groups. Although SrAp-MTA composites did not show statistically significant superiority over pure MTA after multiple-comparison adjustment, they demonstrated consistent osteogenic trends relative to empty defects. Overall, SrAp reinforcement yields a chemically compatible and structurally stable MTA-based composite that supports an enhanced osteogenic response in vivo without increasing fibrosis, suggesting potential utility in endodontic surgery and bone defect repair; longer-term and quantitative analyses are warranted to optimize SrAp content and confirm long-term performance.
Keywords: mineral trioxide aggregate (MTA); strontium apatite (SrAp); bone regeneration; calcium silicate cements; biomaterial composites; osteoblast activity; tibial bone defect model